Think out of the box - Abd Razak, Dzulkifli (2005)
WHAT has the monsoon and economy in common? Probably not much, except in a negative way. During the monsoon season, many economic activities are affected. For example, it would be too risky for fishermen to go out to sea. For the tourist, it may be too wet to venture outside while for the Malaysian man in the street, it will be just too inconvenient. Consequently, many accept this situation and do little to change it. This is a good example of conventional or "insidethebox" kind of thinking. This type of thinking is very common, especially with those who want to play it safe. And there are plenty of them around. On the other hand, there are those who like to question such conventional wisdom. How about having a yacht race during the monsoon season?